Assessment of Maxillary Premolar Region in Relation to Maxillary Sinus Floor and Buccal Bone Plate: A Cone Beam Computed Tomography Study - Fuentes, Ramón; Arellano-Villalón, Manuel; Soto-Faúndez, Natalia; Arias, Alain; Montiel, Ignacio; Borie, Eduardo; Garay, Ivonne; Dias, Fernando
: The maxillary sinus floor location and the buccal bone plate are factors to be considered in the long-term success with implant treatments mainly in the premolar region. the aim of this study was to establish morphometric characteristics of the buccal cortical bone (BCB) thickness of maxillary premolars and its relation to maxillary sinus floor through CBCT. In this study 350 first and second maxillary premolars were analyzed from 110 CBCT images and the buccal cortical bone (BCB) was measured in a coronal view at the major axis level of each premolar. In addition, in 200 first and second maxillary premolars CBCT images were measured the distance from premolar apex to maxillary sinus floor (MSF) in both frontal and sagittal plane. The type of relationship between the apex and MSF was classified according to Ok et al. (2014). The second premolar was observed with higher values of BCB (p<0.001). In first premolar, higher values were observed in the male sex (p>0.05). In second premolar, only significantly higher values were observed in the male sex in MA-MB-MC (p>0.05). Regarding to MSF and its relation to premolar roots, it was observed that 10 % of the sample was classified as type I, 19 % as type II, 55.5 % as type III and 15.5 % as type IV. The BCB of the upper premolar region is thicker in the apical region and decreases toward the coronal region. Almost 50 % of apex of second premolars are closely and risky related MSF (Type I and II).